Effect of Stocking Density on Growth and Production Performance of Culture of Labeo Rohita (Hamilton, 1822) In Floating Net Cages - Sanitha. S; Dube. K.; Reddy A. K.; Tiwari V. K; R. Vivek (Journal of Indian Fisheries Association, 2018)
An experiment was conducted for the culture of Labeo rohita in floating net cages in the Waki reservoir, Maharashtra, where the fingerlings of initial length 5.4 +0.12cm and weight 1.61 +0.20gm were stocked at different stocking densities i.e., 5,10,20,30,40 and 50 no/m3 in three replicates and reared for 120 days. The mean body weight, weight gain percentage (WG %), specific growth rate (SGR) were found to be highest in the lowest stocking density of 5 no/m3, whereas, lowest growth values were recorded at highest stocking density of 50 no/m There was a significant difference in weight gain percentage (WG %) between the treatments, but the specific growth rate (SGR) was not significantly different from stocking 10,20,30,40 and 50 no/m3. Among the treatments TI, T2, T3 there was no significant difference in survival rate: The production rate was proportional to the stocking density: From the production point of view T6 (50 no/m3 ) with 3.36 kg/m3 can be considered as the best stocking density, but for the grow out culture of fish, the average body weight and survival rate has to be considered as the major factor rather than the final biomass. From the present study, it can be concluded that T1 with an average body weight of 127.80 ±3.30g (20-25 cm) and survival rate 87.46± 0.24% may be considered as optimum stocking density for the grow out culture of Labeo rohita in floating net cages of 3m x3 mx2m size Tor a period of 120 days.